1988
DOI: 10.1021/jm00120a010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiherpetic activity of (.+-.)-9-[[(Z)-2-(hydroxymethyl)cyclopropyl]methyl]guanine and related compounds

Abstract: A series of analogues of acyclovir and ganciclovir were prepared in which conformational constraints were imposed by incorporation of a cyclopropane ring or unsaturation into the side chain. In addition, several related base-modified compounds were synthesized. These acyclonucleosides were evaluated for enzymatic phosphorylation and DNA polymerase inhibition in a staggered assay and for inhibitory activity against herpes simplex virus types 1 and 2 in vitro. Certain of the guanine or 8-azaguanine derivatives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(32 citation statements)
references
References 0 publications
1
30
1
Order By: Relevance
“…The authors concluded that there was no absolute correlation of either triphosphate formation or polymerase inhibition with in vitro antiviral activity against HSV-1. In fact, several compounds were found to be not phosphorylated at all by HSV thymidine kinase in their assay systems and yet exhibited modest antiviral activity (1). Conceivably their compounds as well as T01132 and T70072 may be phosphorylated by other cellular enzymes, or their antiviral activity may be unrelated to phosphorylation or DNA polymerase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that there was no absolute correlation of either triphosphate formation or polymerase inhibition with in vitro antiviral activity against HSV-1. In fact, several compounds were found to be not phosphorylated at all by HSV thymidine kinase in their assay systems and yet exhibited modest antiviral activity (1). Conceivably their compounds as well as T01132 and T70072 may be phosphorylated by other cellular enzymes, or their antiviral activity may be unrelated to phosphorylation or DNA polymerase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…[OTf] could be isolated, in the case of ligands 6-9, the equilibrium between the trifluoroacetate (46-49) and hydride (54)(55)(56)(57) complexes is strongly shifted in favour of the trifluoroacetate complexes. In further contrast to the ALPHA/triflic acid system, the ethyl complexes 61-64 are only stable in the presence of an overpressure of ethene.…”
Section: A C H T U N G T R E N N U N G (Alpha)ha C H T U N G T R E N mentioning
confidence: 99%
“…The other consequence of this structural change could be a conformational constraint (18). It has been shown that the introduction of a rigid structure into nucleosides can promote antiviral properties in certain compounds (1,2,5,18). For example, a conformationally constrained analogue of acyclovir was found to have potent antiherpetic properties (herpes simplex virus type 1 [HSV-1] and HSV-2) comparable to those of the nonconstrained acyclovir (2).…”
mentioning
confidence: 99%
“…It has been shown that the introduction of a rigid structure into nucleosides can promote antiviral properties in certain compounds (1,2,5,18). For example, a conformationally constrained analogue of acyclovir was found to have potent antiherpetic properties (herpes simplex virus type 1 [HSV-1] and HSV-2) comparable to those of the nonconstrained acyclovir (2). The structural rigidity of stavudine (D4T) also appears to play an important role in its antiviral activity (4,5).…”
mentioning
confidence: 99%